Effects of Bosentan on Peripheral Endothelial Function in Patients with Pulmonary Arterial Hypertension or Chronic Thromboembolic Pulmonary Hypertension. (June 2016) - Hirashiki, Akihiro; Adachi, Shiro; Nakano, Yoshihisa; Kamimura, Yoshihiro; Shimokata, Shigetake; Takeshita, Kyosuke; Murohara, Toyoaki; Kondo, Takahisa
Endothelin receptor antagonists (ERAs) have been shown to improve the prognosis of patients with pulmonary arterial hypertension (PAH). However, the effect of the oral dual ERA bosentan on peripheral endothelial dysfunction (PED), as assessed by flow-mediated vasodilation (FMD), in patients with pulmonary hypertension is not well characterized. We investigated the effect of bosentan on PED in patients with PAH or inoperable chronic thromboembolic pulmonary hypertension (CTEPH). A total of 18 patients with PAH and 8 with CTEPH were treated with bosentan. All patients underwent FMD assessment before and after 3 months of bosentan treatment. Whereas FMD increased from 6.01% ± 2.42% at baseline to 8.07% ± 3.18% after 3 months ( P < 0.0001) in patients with PAH, those with CTEPH showed no change in FMD after bosentan therapy. In addition, FMD at baseline showed no correlation with pulmonary vascular resistance ( r = 0.09) or plasma brain natriuretic peptide levels ( r = −0.23) in patients with PAH. Bosentan treatment ameliorated PED in patients with PAH but not in those with inoperable CTEPH. In addition, FMD did not correlate with PAH severity.